Analysis Of Educational Domain Objectives In Social Studies (IPS) For Student Competency Development: A Cognitive, Affective, And Psychomotor Approach - Rammayani, Winda (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
Social Studies (IPS) education plays a vital role in shaping student competencies across cognitive, affective, and psychomotor domains. However, current IPS teaching practices remain heavily focused on cognitive knowledge acquisition, while the development of affective and psychomotor domains receives considerably less attention. Project-Based Learning (PjBL) is considered an effective solution capable of holistically integrating all three domains into the learning process. This study adopts a descriptive qualitative approach using library research methodology by analyzing recent scholarly literature on the implementation of cognitive, affective, and psychomotor domains in project-based Social Studies education. Data were collected from national and international journal articles published within the last five years and analyzed using content analysis techniques to synthesize findings. The review results indicate that the PjBL model not only enhances conceptual understanding (cognitive) but also fosters positive attitudes (affective) and practical skills (psychomotor) among students simultaneously. However, the primary challenges lie in developing holistic assessment instruments and equipping teachers with the necessary skills to effectively apply this approach. This study recommends strengthening teacher capacity, developing integrated assessment tools, and policy support to optimize comprehensive Social Studies education. The findings offer both conceptual and practical contributions to the development of more integrative and meaningful Social Studies learning.